Ekman Boundary Layers and Energy Dissipation in Rotating Drums During Spin-Down Process - Hiroshi Ohue; Genshi Kawashima; Wen-Jei Yang (International Journal of Rotating Machinery, 1995)
The Laser Doppler Velocimetry (LDV) is employed to investigate energy dissipation during a spin-down process inside a rotating drum. The tracer/light sheet method is applied to observe flow patterns in the entire flow field from which the instantaneous, two-dimensional velocity distribution and the formation and subsequent time wise variation of the Ekman boundary layer are determined. Results are synthesized to find the relationship between the Ekman boundary layer and the redistribution of secondary-flow induced angular momentum. The fluid viscosity, drum size and speed of rotation are varied to determine their effects on both the Ekman boundary layer and energy dissipation during spin-down process. The role of Ekman boundary layer in the reduction of rotating fluid motion is determined. Results from the study may be used to develop a method to achieve uniform mixing in an enclosed vessel.